Dialysis after graft loss: a Swiss experience. Issue 12 (14th March 2020) - Bonani, Marco; Achermann, Rita; Seeger, Harald; Scharfe, Michael; Müller, Thomas; Schaub, Stefan; Binet, Isabelle; Huynh-Do, Uyen; Dahdal, Suzan; Golshayan, Dela; Hadaya, Karine; Wüthrich, Rudolf P; et al.
Abstract: Background: Patients returning to dialysis after graft loss have high early morbidity and mortality. Methods: We used data from the Swiss Transplant Cohort Study to describe the current practice and outcomes in Switzerland. All patients who received a renal allograft between May 2008 and December 2014 were included. The patients with graft loss were divided into two groups depending on whether the graft loss occurred within 1 year after transplantation (early graft loss group) or later (late graft loss group). Patients with primary non-function who never gained graft function were excluded. Results: Seventy-seven out of 1502 patients lost their graft during follow-up, 40 within 1 year after transplantation. Eleven patients died within 30 days after allograft loss. Patient survival was 86, 81 and 74% at 30, 90 and 365 days after graft loss, respectively. About 92% started haemodialysis, 62% with definitive vascular access, which was associated with decreased mortality (hazard ratio = 0.28). At the time of graft loss, most patients were on triple immunosuppressive therapy with significant reduction after nephrectomy. One year after graft loss, 77.5% (31 of 40) of patients in the early and 43.2% (16 out of 37) in the late-loss group had undergone nephrectomy. Three years after graft loss, 36% of the patients with early and 12% with late graft loss received another allograft. Conclusion: In summary, our data illustrate high mortality, and a high number of allograft nephrectomies and re-transplantations. Patients commencing haemodialysis with a catheter had significantly higher mortality than patients with definitive access. The role of immunosuppression reduction and allograft nephrectomy as interdependent factors for mortality and re-transplantation needs further evaluation.